Perlindungan Hukum Terhadap Bank Sebagai Pemegang Hak Tanggungan dalam Pemberesan Aset Pailit (Studi Kasus Kepailitan PT. Cowell Development. Tbk) - Pranoto, Arief Alfred (Jurnal Impresi Indonesia, 2025)
The rapidly growing business environment has intensified competition among companies, compelling business actors to expand their operations strategically and accurately. Such expansion requires companies to strengthen their financial resources. However, business growth is often not aligned with proper financial management, leading to instability and imbalance within corporate finances. As a result, many businesses face various challenges, including the risk of bankruptcy, which ultimately forces companies to obtain financial support from banks to sustain their operations. Banks thus become a primary funding solution, with companies securing credit by pledging or mortgaging their assets. This study examines this relationship in the context of corporate bankruptcy and concludes that banks, as creditors, require strong legal protection and certainty regarding the credit they extend, as well as alignment in the implementation of relevant legal provisions. The research employs a normative–empirical legal method, combining statutory analysis, literature review, and interviews with credible sources from banking institutions and companies. The objective is to identify the form of legal protection available to creditors and explore the steps that can be taken by creditors concerning Mortgage Rights when debtors are declared bankrupt. The analysis refers to the interaction and relevance between Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations and Law No. 4 of 1996 on Mortgage Rights over Land and Objects Related to Land in the execution of collateral. The study highlights the importance of harmonizing and synergizing statutory regulations to ensure effective handling of corporate bankruptcy cases. The rapidly growing business environment has intensified competition among companies, compelling business actors to expand their operations strategically and accurately. Such expansion requires companies to strengthen their financial resources. However, business growth is often not aligned with proper financial management, leading to instability and imbalance within corporate finances. As a result, many businesses face various challenges, including the risk of bankruptcy, which ultimately forces companies to obtain financial support from banks to sustain their operations. Banks thus become a primary funding solution, with companies securing credit by pledging or mortgaging their assets. This study examines this relationship in the context of corporate bankruptcy and concludes that banks, as creditors, require strong legal protection and certainty regarding the credit they extend, as well as alignment in the implementation of relevant legal provisions. The research employs a normative–empirical legal method, combining statutory analysis, literature review, and interviews with credible sources from banking institutions and companies. The objective is to identify the form of legal protection available to creditors and explore the steps that can be taken by creditors concerning Mortgage Rights when debtors are declared bankrupt. The analysis refers to the interaction and relevance between Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations and Law No. 4 of 1996 on Mortgage Rights over Land and Objects Related to Land in the execution of collateral. The study highlights the importance of harmonizing and synergizing statutory regulations to ensure effective handling of corporate bankruptcy cases.